Die "Reichskristallnacht" in Schleswig-Holstein. Der Novemberpogrom im historischen Kontext - Hering, Rainer (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2016)
During the Reichspogromnacht between November 9th and 10th, 1938, in Germany and Austria 1400 synagogues and other Jewish institutions as well as thousands of Jewish homes and shops were destroyed. More than 30.000 men were deported, and at least 100 killed.This pogrom, frequently referred to as ,,Reichskristallnacht, marked the beginning of political and economic persecution of Jews in Nazi Germany, and an increasingly brutal treatment of the Jewish minority, thus paving the way for the Holocaust.With regards to the 75th annual recurrence of the Reichspogromnacht, the Landesarchiv Schleswig-Holstein in 2013 presented an exhibition centered around the events of that night in Northern Germany. This exhibition was prepared in close cooperation with the University of Flensburg and the Landeszentrale für politische Bildung Schleswig-Holstein. It was accompanied by a series of lectures that are included in this book as well as some of the illustrations displayed."